The contribution of livestock to soil fertility - Tarawali, Shirley A.; Larbi, Asamoah; Fernández Rivera, S.; Bationo, B. André (SSSA, 2001)
In response to on-going agricultural intensification, crop-livestock systems are becoming more important in West African farming systems. The role of livestock in providing stability to such systems, particularly through their interaction with the soil environment is unquestionable. Worldwide, the value of livestock manure has been estimated to be equivalent to inorganic fertilizer valued up to U.S. $1.5 billion annually. Focusing on the dry savanna regions of West Africa, this chapter reviews research on the evolution of crop-livestock systems, and the contribution of livestock to soil fertility, outlines some present key research issues and discusses these .with regard to livestock-soil interactions in the future. In this context, the influence of ruminant livestock on soil chemical, physical, and biological properties, soil organic matter and nutrient contents, as well as strategies to maximize nutrient capture and utilization are considered. Livestock effects on soil physical properties are rarely negative, unless movement is restricted and the animal density becomes excessively high. Livestock also plays a role in cycling nutrients and in transporting them from rangeland to cropland. The influence of livestock on soil fertility is also mitigated by their diet and can be improved by introducing legumes or improving crop residue quantity/quality.